[Retracted] Conservative Therapy vs. Endovascular Approach for Intracranial Vertebrobasilar Artery Trunk Large Aneurysms: A Prospective Multicenter Cohort Study - Wu, Qiaowei; Li, Tianxiao; Jiang, Weijian; Hernesniemi, Juha Antero; Li, Li; He, Yingkun (Oxidative Medicine and Cellular Longevity, 2022)
Background. Intracranial vertebrobasilar trunk large (≥10 mm) aneurysms (IVBTLAs) are rare and challenging to manage. In this study, we describe the natural prognosis and evaluate the safety and efficacy of endovascular treatment of IVBTLAs compared with conservative therapy. Methods. This prospective multicenter cohort study included patients with IVBTLAs, who chose either endovascular treatment (endovascular group) or conservative therapy (conservative group) after discussion with their doctors. The primary endpoint was the incidence of serious adverse events (SAEs) related to the target vessel, while secondary endpoints included target vessel-related mortality, major stroke, other serious adverse events, and aneurysm occlusion rate. Results. In total, 258 patients were referred to our two centers for the management of vertebrobasilar aneurysms, and 69 patients had IVBTLAs. Among them, 51 patients underwent endovascular treatment, and 18 patients received conservative therapy. The incidence of target vessel-related SAEs was 15.7% (8/51) in the endovascular group and 44.4% (8/18) in the conservative group (P=0.031). The target vessel-related mortality was 2.0% (1/51) in the endovascular group and 38.9% (7/18) in the conservative group (P<0.001). The cumulative survival rates in the endovascular group and conservative group within 1-year, 3-year, and 5-year were 98.0% vs. 83.3%, P=0.020; 98.0% vs. 66.7%, P=0.001; and 98.0% vs. 35.6%, P<0.001, respectively. Multivariate analysis revealed conservative therapy, giant aneurysm, and ischemic onset as risks factor for SAEs. Conclusions. Compared with conservative treatment, endovascular treatment of the IVBTLAs may be associated with a lower incidence of SAEs, with higher 1-year, 3-year, and 5-year survival rates. Conservative therapy, giant aneurysm, and ischemic onset were associated with a high risk of SAEs.